BENTUK AFIKS DALAM LIRIK LAGU SEDIA AKU SEBELUM HUJAN KARYA IDGITAF KAJIAN MORFOLOGI - Dina Sri Puspitasari; Dinda Wulansari; Khusnul Nur Mawar Sari; Mita Miftaqul Muhclisah (CV. Denasya Smart Publisher, 2026)
This study aims to examine the word formation process through affixation in the lyrics of the song